1982
DOI: 10.1111/j.1532-5415.1982.tb05064.x
|View full text |Cite
|
Sign up to set email alerts
|

Observations on Lithium Disposition in the Elderly

Abstract: The disposition kinetics of lithium were studied in six elderly women who had been maintained on this medication for several years. Lithium administration was stopped abruptly. Plasma, whole blood, and erythrocyte half-lives were then measured, as well as renal plasma clearance and distribution volume. Half-life values in whole blood and in its components were found to be similar. The plasma lithium half-life approximated that in younger schizophrenics, but appeared prolonged when compared with half-lives repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Mason et al (1978) estimated the elimination half-life in a group of schizophrenic patients to be, on average, 28.9 h, and as in our study there were considerable interindividual variations. Chapron et al (1982) found similar values in a group of elderly women with affective disorders in whom the mean treatment time with lithium was 3 years. Nielsen-Kudsk and Amdisen (1979) demonstrated an elimination half-life of 19.8 h in healthy volunteers, but the interindividual difference was substantial.…”
Section: Discussionsupporting
confidence: 82%
“…Mason et al (1978) estimated the elimination half-life in a group of schizophrenic patients to be, on average, 28.9 h, and as in our study there were considerable interindividual variations. Chapron et al (1982) found similar values in a group of elderly women with affective disorders in whom the mean treatment time with lithium was 3 years. Nielsen-Kudsk and Amdisen (1979) demonstrated an elimination half-life of 19.8 h in healthy volunteers, but the interindividual difference was substantial.…”
Section: Discussionsupporting
confidence: 82%
“…Inclusion of children in their study or the confounding influence of concurrent heart disease could account for the discrepancy. Previous studies from our laboratory have shown that the ratio of renal drug clearance to creatinine clearance is similar between young and old adults for theophylline (Antal et al, 1981) and lithium (Chapron et al, 1982). The rate of excretion of an intravenous dose of AZ was nearly identical for old and young (Figure 3).…”
Section: Discussionmentioning
confidence: 65%
“…Case notes from 82 patients (21 to 84 years) were reviewed for lithium concentrations, demographic information, concurrent medications or medical conditions and clinical assessments. Chapron et al (1982) reported on 6 female patients aged 73 to 88 years who had been treated with varying doses of lithium for 2 to 5 years. A less marked decline in CSs occurred with increasing age.…”
Section: Lithiummentioning
confidence: 99%